1998
DOI: 10.1038/sj.gt.3300622
|View full text |Cite
|
Sign up to set email alerts
|

Systemic action of human growth hormone following adenovirus-mediated gene transfer to rat submandibular glands

Abstract: We have previously suggested that although salivary were approximately 16 ng/ml and rat insulin-like growth glands function in an exocrine manner they might none the factor-1 was elevated approximately 25%. Moreover, less offer a useful way to deliver therapeutic proteins sysserum chemistry profiles of rats subjected to in vivo gene temically. As a direct functional test of this hypothesis, we transfer displayed alterations in the BUN:creatinine ratio constructed a recombinant adenovirus (AdCMVhGH) and trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 22 publications
6
96
0
2
Order By: Relevance
“…First-generation, E1 − , recombinant adenoviruses (serotype 5) encoding either hEpo (AdCMVhEpo), hEpo-hGH (AdCMVhEpo-hGH), hGH-hEpo (AdCMVhGH-hEpo), or hGH (AdCMVhGH) were constructed as previously reported [25] by contransfection of the shuttle plasmid pAC-CMV-pLpA with the corresponding transgenes, together with the adenoviral plasmid pJM17 into 293 human embryonic kidney (HEK) cells. The vectors were amplified in HEK 293 cells and purified by two rounds of CsCl gradient centrifugation as described [26].…”
Section: Recombinant Adenoviral Vectormentioning
confidence: 99%
“…First-generation, E1 − , recombinant adenoviruses (serotype 5) encoding either hEpo (AdCMVhEpo), hEpo-hGH (AdCMVhEpo-hGH), hGH-hEpo (AdCMVhGH-hEpo), or hGH (AdCMVhGH) were constructed as previously reported [25] by contransfection of the shuttle plasmid pAC-CMV-pLpA with the corresponding transgenes, together with the adenoviral plasmid pJM17 into 293 human embryonic kidney (HEK) cells. The vectors were amplified in HEK 293 cells and purified by two rounds of CsCl gradient centrifugation as described [26].…”
Section: Recombinant Adenoviral Vectormentioning
confidence: 99%
“…Nonetheless, we and others were sufficiently intrigued by this existing body of information to propose a unique application of gene transfer technology to salivary glands; treating systemic single protein deficiency disorders through the endocrine secretion of transgenic secretory proteins (systemic gene therapeutics; Kagami et al, 1996;Goldfine et al, 1997;Wang et al, 1997;He et al, 1998;Niedzinski et al, 2003, see below).…”
Section: Evidence Of Endocrine Secretion From Salivary Glandsmentioning
confidence: 99%
“…For instance, the administration of an adenovirus encoding human growth hormone protein to the SG resulted in systemic protein expression. [2][3][4][5] More recently, we have demonstrated that systemic protein expression can also be obtained with nonviral DNA formulations. 6 Although administration of viral-based vectors to the SGs of experimental animals results in therapeutic concentrations of protein in blood, the recent complications that have occurred in clinical studies have increased concerns about the general safety of viral technologies.…”
Section: Introductionmentioning
confidence: 99%